2001
DOI: 10.1103/physreve.64.021110
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of canonical-dissipative systems and applications to swarm dynamics

Abstract: We develop the theory of canonical-dissipative systems, based on the assumption that both the conservative and the dissipative elements of the dynamics are determined by invariants of motion. In this case, known solutions for conservative systems can be used for an extension of the dynamics, which also includes elements such as the takeup/dissipation of energy. This way, a rather complex dynamics can be mapped to an analytically tractable model, while still covering important features of nonequilibrium systems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 31 publications
3
97
0
2
Order By: Relevance
“…In the context of animal societies, sharp transitions of collective behavior have been reported to occur at specific values of the population density (see for instance [18,30,1,13,15,29,28,22]). As it has been already mentioned in the introduction, models belonging to the same class as Vicsek's exhibit an order-disordered phase transition at a critical value of the particle density.…”
Section: Group Cohesion: the Role Of Density And Interparticle Distancesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of animal societies, sharp transitions of collective behavior have been reported to occur at specific values of the population density (see for instance [18,30,1,13,15,29,28,22]). As it has been already mentioned in the introduction, models belonging to the same class as Vicsek's exhibit an order-disordered phase transition at a critical value of the particle density.…”
Section: Group Cohesion: the Role Of Density And Interparticle Distancesmentioning
confidence: 99%
“…From a purely deterministic perspective, such systems can be represented as high dimensional dynamical systems, which can be either discrete or continuous in their time evolution. This approach has been mainly spearheaded by Smale and collaborators [26,27,18,21]. On the other hand, providing understanding of the connection between macroscopic collective features and microscopic scale interactions in multi-particle systems is well within the principal aims of statistical physics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us replace γ 0 by a function γ(v) and the constant D 0 also by a function D(v). Then we speak about "nonlinear Brownian motion" [1,2], while in other connection we speak about "active Brownian movement" [3][4][5][6]. The corresponding Langevin equation of motion reads:…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the concept of canonical-dissipative systems has been developed to address self-propagating systems, self-excited systems, and in particular limitcycle oscillators that are supplied by energy sources [1][2][3][4][5]. Several studies have demonstrated that the canonical-dissipative approach can yield helpful insights into this kind of open systems [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%